PERAN APOTEKER KLINIS DALAM MENGATASI DRPS TERAPI ANTIBIOTIK: TINJAUAN SISTEMATIS - Syam, Ricky Aditya (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
This study aims to explore the role of clinical pharmacy in overcoming drug-related problems (DRPs) related to antibiotic therapy through a systematic literature review. Antibiotics are essential in treating infections, but their increased use also brings new challenges in the form of DRPs that can affect the effectiveness of therapy and patient safety. The method used in this study follows the PRISMA 2020 guidelines by conducting a search in the Wiley and Google Scholar databases for articles published between 2020 and 2025. Of the 103 articles found, seven articles met the inclusion criteria set. The results showed that clinical pharmacists play a critical role in identifying and addressing issues related to antibiotic use. This includes assessing the appropriateness of indications, dosages, and treatment length. The partnership between clinical pharmacists and healthcare teams has resulted in better clinical results. Furthermore, educating patients on the correct use of antibiotics can improve adherence and lower the likelihood of drug-related problems (DRPs). These findings underscore the importance of clinical pharmacist involvement in the management of antibiotic therapy to improve patient safety and treatment effectiveness.